PENGEMBANGAN SUMBER DAYA MANUSIA, KETERAMPILAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA IV REGIONAL I - Andini, Nisa; Nasution, Fitra Arlina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study was conducted at PT. Perkebunan Nusantara IV Regional I to evaluate the simultaneous and partial effects of human resource development, skills, and communication on employee performance. The sample consisted of 57 respondents selected using saturated sampling techniques. Data were collected through observation, questionnaires, and documentation studies, and analyzed using SPSS 25 for data quality testing, classical assumptions, multiple linear regression and hypotheses. The results showed that human resource development, skills, and communication simultaneously and partially had a positive and significant effect on employee performance at PT. Perkebunan Nusantara IV Regional I.